Harmonisasi Tata Kelola Perilaku Siber Siswa Sekolah Dasar: Kemitraan Strategis Administrasi Sekolah dan Pendampingan Keluarga - Supriadi Supriadi; Ummu Kalsum Amaliyah (Lembaga Yasin AlSys, 2026)
The development of digital technology in elementary education has changed students’ learning interaction patterns, particularly in the use of digital devices as informal learning media in the home environment. This study aims to analyze the harmonization of students’ cyber behavior governance through a strategic partnership between school administration and family guidance. This study used a descriptive qualitative approach involving fourth-grade students of SDN 2 Lasusua as the main informants. Data were collected through semi-structured interviews, indirect observation, and confirmation of learning documents. The data were analyzed using the Miles and Huberman interactive model through the stages of data condensation, data display, and conclusion drawing. The results showed that the school had integrated digital technology into learning through an internet-based assignment system that encouraged students to learn independently at home. On the other hand, families played an important role in guiding cyber behavior through three patterns, namely active co-regulation, peer mediation, and autonomous responsibility. The research findings also showed that students had initial ability to identify artificial intelligence-based digital content manipulation. The conclusion of this study affirms that the success of students’ cyber behavior governance is strongly determined by the synergy between school institutions and the family environment in building a safe, productive, and educational digital ecosystem. The implications of this study emphasize the importance of strengthening school-family communication policies, students’ digital literacy, and family guidance that is adaptive to technological development.